A Study Guide to The Fabric of Reform. (International Monetary Fund, 2000)
This guide is designed to facilitate classroom use of The Fabric of Reform, a 30-minute educational video created by the International Monetary Fund. It is intended for use with students in economics and international relations courses at the secondary and postsecondary levels.